Synthesis of Novel N-Aryl-1H-indazolamines from Amino-1H-indazoles and Arylboronic Acids - Kumara Swamy, Udutha; Rama Mohan, H.; Viplava Prasad, U. (Asian Journal of Chemistry, 2014)
An efficient and high-yielding synthesis of N-aryl-1H-indazolamines from amino-1H-indazole and arylboronic acids are described. In this study a series of novel N-aryl-1H-indazolamines (1a-i) were synthesized using arylboronic acids and amino-1H-indazoles (3a-c).